199k views
0 votes
4TH TIME ASKING THIS!!! Please help me! Someone pleaseeee. I need the correct answers. I don’t want to fail

4TH TIME ASKING THIS!!! Please help me! Someone pleaseeee. I need the correct answers-example-1

1 Answer

2 votes

Answer:

The functions are inverses; f(g(x)) = x ⇒ answer D


h^(-1)(x)=\sqrt{(x+1)/(3)} ⇒ answer D

Explanation:

* Lets explain how to find the inverse of a function

- Let f(x) = y

- Exchange x and y

- Solve to find the new y

- The new y =
f^(-1)(x)

* Lets use these steps to solve the problems


f(x)=√(x-3)

∵ f(x) = y


y=√(x-3)

- Exchange x and y


x=√(y-3)

- Square the two sides

∴ x² = y - 3

- Add 3 to both sides

∴ x² + 3 = y

- Change y by
f^(-1)(x)


f^(-1)(x)=x^(2)+3

∵ g(x) = x² + 3


f^(-1)(x)=g(x)

The functions are inverses to each other

* Now lets find f(g(x))

- To find f(g(x)) substitute x in f(x) by g(x)


f(x)=√(x-3)

∵ g(x) = x² + 3


f(g(x))=\sqrt{(x^(2)+3)-3}=\sqrt{x^(2)+3-3}=\sqrt{x^(2)}=x

f(g(x)) = x

The functions are inverses; f(g(x)) = x

* Lets find the inverse of h(x)

∵ h(x) = 3x² - 1 where x ≥ 0

- Let h(x) = y

∴ y = 3x² - 1

- Exchange x and y

∴ x = 3y² - 1

- Add 1 to both sides

∴ x + 1 = 3y²

- Divide both sides by 3


(x + 1)/(3)=y^(2)

- Take √ for both sides

∴ ±
\sqrt{(x+1)/(3)}=y

∵ x ≥ 0

∴ We will chose the positive value of the square root


\sqrt{(x+1)/(3)}=y

- replace y by
h^(-1)(x)


h^(-1)(x)=\sqrt{(x+1)/(3)}

User Mashanna
by
4.9k points